2012
DOI: 10.2196/jmir.2162
|View full text |Cite
|
Sign up to set email alerts
|

Online Advertising to Reach and Recruit Latino Smokers to an Internet Cessation Program: Impact and Costs

Abstract: BackgroundTobacco cessation among Latinos is a public health priority in the United States, particularly given the relatively high growth of this population segment. Although a substantial percentage of American Latinos use the Internet, they have not engaged in Web-based cessation programs as readily as other racial/ethnic subgroups. A lack of culturally specific advertising efforts may partly explain this disparity.ObjectivePhase I of this study focused on the development of four Spanish-language online bann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 52 publications
2
51
0
Order By: Relevance
“…Among these, 13 studies targeted local regions within a country [15,18,22,23,26,27,30,33-35,37,40,42], 8 studies [14,19,28,31,35,38,39,41] targeted recruitment nationally, and 2 studies targeted recruitment internationally [16,36]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 13 studies targeted local regions within a country [15,18,22,23,26,27,30,33-35,37,40,42], 8 studies [14,19,28,31,35,38,39,41] targeted recruitment nationally, and 2 studies targeted recruitment internationally [16,36]. …”
Section: Resultsmentioning
confidence: 99%
“…A total of 13 studies directly compared cost-effectiveness across different recruitment strategies [15,16,19,20,28,31,33,34,36,37,39,41,42], and the results are presented in Table 2. The cost of advertisement on social media websites was determined by bidding prices for ads, which varied on a daily basis, or the cost of placing a banner ad on a particular website.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most research reporting on Facebookbased recruitment efforts with adolescents or young adults has been with online surveys and internet interventions [7,8,23]. That is, participants are recruited online and immediately connected with an online survey or intervention.…”
Section: Discussionmentioning
confidence: 99%
“…15 One study, which compared traditional with online advertisement recruitment found that men, young adults, ethnic minorities, and a high school education or less were more likely to be recruited via online advertizing. 19 In the current study, we were able to adjust the targeting strategy based on an interim analysis of key characteristics, thereby optimizing the study sample composition; the focused targeting strategy applied during the second phase was successful in increasing the proportion of lower educated women and women with a migrant background.…”
Section: Discussionmentioning
confidence: 94%